Correlación entre las concentraciones urinarias de malondialdehido y el daño en el ADN de personas expuestas al mercurio (2014)
ABSTRACT: To determine whether the extent of DNA damage correlates with the concentration of malondialdehyde (MDA) in urine of individuals occupationally exposed to mercury. Methods: We evaluated 64 medical records (32 from exposed persons and 32 from unexposed controls). In both groups we analyzed the comet assay data (percentage of DNA in the tail), as well as the levels of MDA and mercury in the urine. We compared the MDA concentrations, and the changes in the comet assay between the groups and the correlation between these variables. Results: MDA concentrations were higher in exposed persons than in controls (median 1.28 vs. 0.51 μmol/L, respectively), and a corresponding damage was observed in the comet assay (median of DNA percentage in tail: 27.37 vs. 0.31, respectively). However, we found poor correlation between urinary MDA and genetic damage (r <0.11). Conclusion: No evidence was obtained indicating that higher concentrations of MDA in urine were related to additional genetic damage, but there were more DNA damage and higher concentrations of MDA in individuals occupationally exposed to mercury compared with unexposed people.